ANALYSIS OF THE DEVELOPMENT POTENTIAL OF ECOTOURISM OBJECTS IN INDRAGIRI HULU DISTRICT - Suwaji, Suwaji; Apriansyah, Roky; Heriasman, Heriasman; Gustika, Gita Sari; Warnadi, Warnadi (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
Indragiri Hulu Regency has quite diverse natural tourism potential (Ecotourism). Natural tourist attractions are tourist characteristics that are in great demand by tourists, the main attraction is the scenery and natural physical symptoms they have. This research aims to analyze the feasibility of potential natural tourism objects in Indragiri Hulu Regency. Field observation and interviews with designated key informants carried out primary data collection. The analysis used in the research includes feasibility analysis which refers to the 2003 Directorate General of Forest Protection and Nature Conservation's Operation Area Analysis of Natural Tourist Attraction Objects (ADO-ODTWA) guidelines. Based on these guidelines, an assessment is carried out on the variables where each variable's weight has been determined. value. The assessment of each variable begins with determining a score for each variable, determining the feasibility index value. Based on the index value, the classification or level of feasibility of the object under study can be determined. The research results show that 4 of the 6 objects have a high feasibility index, namely the Lake Raja tourist attraction, the Bukit Tigapuluh National Park tourist attraction, the Menduyan Lake tourist attraction and the Kembar Lake tourist attraction. Meanwhile, the other 2 objects, namely the Tembulun Berasap Waterfall Tourist Attraction, and the Denalo Waterfall are still in the medium or unsuitable category. The feasibility of an object's potential is contributed more by the object's attractiveness variables, the availability of clean water and supporting conditions around the area, management and service variables, and supporting facilities still in the not yet feasible category. The accessibility factor is also a key to connectivity, and On average, the availability of accommodation for tourists' comfort is still in the inadequate category.